Patient Concerns About Human Papillomavirus Testing and 5-Year Intervals in Routine Cervical Cancer Screening - Silver, Michelle I. (Obstet Gynecol, 2015)
OBJECTIVE: To explore attitudes towards new cervical cancer screening options and understand factors associated with those beliefs among women in routine gynecologic care. METHODS: We used an interviewer-administered survey of 551 women aged 36–62 years enrolled in the HPV in Perimenopause Study. Poisson regression with robust error variance was used to estimate prevalence ratios and 95% confidence intervals to compare women’s preferences for cervical cancer screening methods and frequency. RESULTS: A majority of women (55.6%, 95%CI: 51.4–59.8%) were aware that screening recommendations had changed, yet 74.1% (95%CI: 70.3–77.7%) still believed women should be screened annually. If recommended by their doctor, 68.4% (95% CI: 64.4–72.2%) were willing to extend screening to every three years, but only 25.2% (95%CI: 21.9–29.2%) would extend screening to five years. Most women (60.7%, 95%CI: 56.5–65.7%) expressed a strong preference for Pap testing, and 41.4% (95%CI: 37.4–45.6%) expressed at least moderate concern over having an HPV test without a Pap test. A desire for more frequent care, higher degree of worry and perceived risk, and abnormal screening history were all associated with reduced willingness to accept HPV testing and longer screening intervals. CONCLUSION: A majority of routinely screened women indicated a willingness to adopt a cervical cancer screening strategy of cytology alone or Pap-HPV co-testing every 3 years if recommended by their physician. However, they remain concerned about HPV testing and extension of screening intervals to once every 5 years. Our results suggest continued reticence to accepting newer HPV-based screening algorithms among routinely screened women over age 35 years.